Ülker Company: Achieving Success in the Middle East Region and Beyond - Hanaysha, Jalal (IIUM Journal of Case Studies in Management, 2025)
Ülker is a well-established brand which has witnessed a remarkable success in Turkey and international markets. Ülker Bisküvi started its journey in a small workshop in 1944. Currently, it offers a wide range of products in the biscuit, cake and chocolate categories. Ülker exports more than 300 brands to over 100 countries worldwide. It has also successfully developed its international operations and rich product portfolio. Moving beyond Turkey, the company continues to lead the biscuit market in Egypt and Saudi Arabia, and maintains its robust position in Kazakhstan and other countries. Ülker maintained its position and leadership in the markets in which it operates through improving its production, supply and logistics infrastructure as well as expanding its investments in R&D, innovation, digitalization and sustainability. This case study enhances our understanding about the historical developments in Ülker’s journey towards success both in local and international markets. It also enables us to comprehend that factors that contributed the success of the company along with the entry modes adopted for international expansion. Key emphasis is placed on marketing mix strategies of Ülker in target markets. The case also outlines about the initiatives adopted by Ülker for embracing sustainability and managing its human resources. Finally, it highlights the approaches used by the company for effective risk management.